THE IMPLEMENTATION OF BLENDED LEARNING MODEL BASED ON EDMODO TO IMPROVE STUDENTS’ LEARNING MOTIVATION AND ACHIEVEMENT - Fauziyah Sulistiani; Sukirno Sukirno (Jurnal Pendidikan Akuntansi Indonesia, 2016)
This research is an action research that aims to improve students’ learning motivation and achievements class X Accounting 2 SMK N 7 Yogyakarta academic year 2015/2016 by the implementation of Blended Learning Model based on Edmodo. Data Analysis Technique was by descriptive comparative. Based on research results, it can concluded that the implementation of Blended Learning teaching technique based on Edmodo can improve students’ learning motivation and achievements of X Accounting 2 of SMK N 7 Yogyakarta academic year 2015/2016. It is supported by research findings that percentage of learning motivation of Accounting increased to 6,87% from 74,22% in first cycle to 81,09% in second cycle. Based on learning achievements of Acounting, students’ mean score increased 8,9% from mean score of pretest 70,15 to 76,40 in post test in first cycle. In second cycle, there is an increase 7,78 points from 75,59 in pretest to 83,37 in post test. In addition, completion study mean score also increased 18,75%, from 65,63% in first cycle to 84,38% in second cycle.  Keywords: Blended learning, Edmodo, Learning Motivation and Achievements of Accounting.